Exploring the conditions that promote intergroup contact at urban parks. (27th May 2022) - Powers, Samantha L.; Graefe, Alan R.; Benfield, Jacob A.; Hickerson, Benjamin; Baker, Birgitta L.; Mullenbach, Lauren E.; Mowen, Andrew J.
Abstract: Urban parks have the potential to serve as places that facilitate intergroup contact between racially and ethnically diverse users. However, there is limited evidence identifying the conditions under which intergroup contact occurs in urban park settings. Existing literature suggests that the psychosocial conditions of safety, community engagement, psychological ownership, and sense of welcome and belonging may be related to park-based intergroup contact. The purpose of this study was to test the hypothesized structural relationships between these factors and intergroup contact among park visitors at three parks in Philadelphia, PA ( n  = 324). Results demonstrated that intergroup contact is more common when visitors feel a greater sense of welcome and belonging at parks. Moreover, indirect relationships suggest that efforts to engage community residents in decision making, stimulate psychological ownership, and improve safety can help diverse users to feel more welcome, and in turn, engage in more intergroup contact.